مفهوم التعارض وكليات الجمع عند الإمام الشاطبي: دراسة مقارنة - 'Abd Allah Nasih 'Ulwan, Umar (Jurnal Syariah, 2010)
This study demonstrates that Imam Shatibi (may Allah have mercy on him) formed an innovative approach for studying the subject of the principles of Islamic jurisprudence (Usul al-Fiqh). It is a distinctive approach with unique features that suit every subject matter related to Usul al-Fiqh and is different from the approaches and methodologies of mutakalimin (proponents of philosophy) and fuqaha’ (jurists). It is an integrated approach that links between laying the foundations of the issues of the principles of Islamic law on the purposive approach of Islamic Jurisprudence and its practical applications; and it also links between the particulars and the universals of Islamic Jurisprudence. Consequently, this method gives a suitable legislating position to both particulars and the universals in a manner in which they are not overshadowed by each other. The research will show how Imam Shatibi excelled among all jurists in addressing the subject of contradictions and preference, an important subject in which different opinions are given on an issue and among them only one opinion is chosen and preferred by an adequate justification.